The relevance of emotions during M&As - Hannuksela, Saana (My University, 2018)
Merger and acquisitions (M&AS) are an integral part of today´s business environment. The number of M&As has risen year by year and in general they are executed in expectations of financial benefit in the future. Even though companies are willing to invest in M&As financially and legally, the transactions are more supposed to fail than succeed. The reason for that can be seen in the so called soft issues like human resource functions. The importance of HRM during M&As is based on the change management literatures assumption of individual as a base of the organizational change. The role of HR is instead, to support individual in his/her own change process influenced by a M&A. In addition to HR practices, emotions are affecting to the individual´s change process through the attitude towards change. Even though the emotions are known to be an indispensable part of change process in general, their importance during M&A is very little studied and acknowledged in HR. For that reason, the main purpose of this research is to examine the relevance of emotions during M&A process. Emotions are explored from psychological perspective because it provides wider and deeper understanding on emotions. Previous studies have mainly considered emotions from general change management perspective which means that their importance and potential during M&A has been totally ignored and they are have been seen as a human frailty and negative aspect from successful M&A´s perspective. For that reason, many positive aspects rising from emotions has been totally neglected in previous studies. The interviews of the research were hold in narrative sense because with the help of that, the interviews about emotions and experiences are richer and more open, and they can provide more information than non-narrative interviews. Narrative analysis also emphasizes and supports the subjective and free expression of experiences because any prior hypotheses or propositions are not made in advance. The research data was collected from eight employees who were acquired successfully lately. The interviews were analysed narratively and eight different emotional stories of M&As were structured. Based on the research data and psychological perspective, emotions can be seen relevant during the M&A process. To clarify, both negative and positive emotions help employees to construct the meaning of change. In addition to this, diverse emotions are an integral part of individual´s change process and they reveal if something is important or relevant from individual´s point of view. Emotions can also reveal important data of change process to HR and that can be used to support an individual and improve the transaction process. The need of stability during the process and its connection to the feel of safety also reveal, how relevant emotions are during the M&A process. All these aspects are also influencing to the satisfaction towards change and the one´s willingness to change and from that light are for its part increasing the probability of successful M&A.
Keywords: M&A; HR; individual´s change process; emotions; psychological perspective; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Henkilöstöjohtamisen maisteriohjelma|en=Master's Programme in Human Resource Managment|